2021
DOI: 10.7759/cureus.19084
|View full text |Cite
|
Sign up to set email alerts
|

Acute Endothelial Graft Rejection Following COVID-19 Infection

Abstract: Here, we report a case of acute endothelial graft rejection following coronavirus disease 2019 (COVID-19). A 57-year-old woman who underwent therapeutic penetrating keratoplasty for a perforated infectious corneal ulcer in her right eye developed severe acute respiratory syndrome coronavirus 2 infection, which required intensive care and treatment with steroids. Acute endothelial graft rejection was seen at three weeks postoperatively and managed with high-dose corticosteroids. Despite standard therapy, second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…After the exclusion of duplicates and articles that did not fulfill the study inclusion criteria, fifty-two articles were included in the qualitative synthesis of this systematic review. The reports of ninety-six cases (fiftysix organ rejection cases following COVID-19 vaccination [7][8][9][10][11] and forty organ rejection cases after COVID-19 infection [12][13][14][15][16][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]) identified from these articles are presented in groups based on confirmed diagnoses, laboratory, biopsy and imaging findings. The detailed characteristics of the included studies are shown in Tables 1 and 2.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…After the exclusion of duplicates and articles that did not fulfill the study inclusion criteria, fifty-two articles were included in the qualitative synthesis of this systematic review. The reports of ninety-six cases (fiftysix organ rejection cases following COVID-19 vaccination [7][8][9][10][11] and forty organ rejection cases after COVID-19 infection [12][13][14][15][16][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]) identified from these articles are presented in groups based on confirmed diagnoses, laboratory, biopsy and imaging findings. The detailed characteristics of the included studies are shown in Tables 1 and 2.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Cells in the anterior chamber There were 42 case reports [5][6][7][8][11][12][13]17,18,[20][21][22][24][25][26][27][29][30][31][32][33][34][35][37][38][39][40][41][42][43][44][45][48][49][50][51][52][53][54][55][56][57], 8 case series [9,10,14,28,36,46,47,58] and 2 cohort studies [19,23]. These studies were conducted in t...…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Twenty-four articles were identified through the database search on 13 February 2022 [ 20 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. After reviewing the titles and abstracts of the 24 articles, 10 were excluded based on the article type (letter to the editor and review) [ 44 , 47 ], corneal graft rejection after COVID-19 [ 45 , 46 , 48 , 50 ], eye banking issues during the COVID-19 pandemic [ 42 , 49 ], and other unrelated topics [ 43 , 51 ]. Fourteen articles were selected for full-text screening, and one was excluded because of the lack of clinical history [ 20 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another important limitation is that the number of publications on acute rejection after SARS‐CoV‐2 vaccination exceeds by far the number of reports of keratoplasty patients developing corneal allograft rejection after other vaccines; while this is possibly due to increased awareness of the potential of immunization‐induced immune reactions on corneal grafts, it is also possible that the novelty of the viral agent and the novelty of the mRNA vaccines raised a potential publication bias. We emphasize our belief that the benefits of SARS‐CoV‐2 vaccination far outweigh the potential risks of acute corneal allograft rejection following vaccination, considering the potentially severe complications of COVID‐19 disease, and considering the potential ocular manifestations of COVID‐19 (Cunha et al, 2020 ), which may also include acute corneal graft rejection (Ang et al, 2020 ; Behera et al, 2021 ; Jin & Juthani, 2020 ; Singh & Mathur, 2021 ). Most corneal surgeons agree with this policy, according to a recent survey of 142 corneal surgeons (Lockington et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%